Pendidikan Holistik untuk Anak Usia Dini: Menelaah Pemikiran Imam Al-Ghazali tentang Pendidikan Integratif - Nihwan, Nihwan; Primanisa, Reiska (Prodi PIAUD STAI Sumatera Medan, 2024)
This study aims to examine the concept of holistic education in the thought of Imam Al-Ghazali and its relevance to early childhood education in the modern era. Using a qualitative method with a literature study approach, this research analyzes Al-Ghazali’s major works such as Ihya’ Ulumuddin, Ayyuha al-Walad, Mizan al-Amal, and Al-Tarbiyah al-Islamiyyah wa Madrasatuh. The findings reveal that Al-Ghazali’s concept of holistic education is rooted in the view of humans as integrated beings—comprising body, intellect, and soul. The ultimate goal of education, according to Al-Ghazali, is the formation of insan kamil (the complete human), who achieves balance across physical, intellectual, emotional, and spiritual dimensions. His educational philosophy aligns with the Holistic Integrative Early Childhood Education paradigm in Indonesia but adds a spiritual dimension as the core of human development. Its practical implications include moral value-based learning, teacher role modeling, balance between cognitive and physical activities, and spiritual habituation. The novelty of this study lies in synthesizing Al-Ghazali’s classical educational thought with contemporary early childhood education practices, producing a paradigm of “transcendental holistic education” grounded in Islamic values and responsive to the challenges of modern education.